PENGARUH SPESIALISASI INDUSTRI AUDITOR DAN REPUTASI AUDITOR TERHADAP AUDIT REPORT LAG (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018 dan 2019) - Khairunnisa, Amira Fathia; Syafruddin, Muchamad (Diponegoro Journal of Accounting, 2021)
This study aims to empirically examine the Effect of Auditor Industry Specialization and Reputation Auditor on Audit Report Lag (Empirical Study of Manufacturing Companies Listed on the Indonesia Stock Exchange in 2018 and 2019). The population in this study were all companies registered in Indonesia Stock Exchange for the year 2018 and 2019. The data used in this study were secondary data and the sampling method used purposive sampling. Total number of samples used in this study were 202 study samples. The data in this study were analyzed using multiple regression techniques. Before being conducted by regression test, it was examined by using classical assumption test. Other than classical assumption test, the data in this study were also analyzed using pearson and spearman correlation test. The results of this study indicate that auditor industry specialization has negative and significant effect to the audit report lag. While, reputation auditor is not significantly influence to the audit report lag.